HOW HYBRID IS SAINT LUCIAN LAW? - Huxley, Andrew (Revue générale de droit)

(untitled) (Éditions de l’Université d’Ottawa, 1983)
Following the introduction of English Law into the Civil Code of St. Lucia in 1956, a number of questions are raised about the possible influence of English case law in St. Lucia.